PENGARUH SURAT TAGIHAN PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK PRATAMA PONDOK AREN (2019- 2023) - Luthfiyah Avifah; Desi Kurniawati (Journal of Research and Publication Innovation, 2026)
This study aims to analyze the effect of Tax Collection Letter (Surat Tagihan Pajak) and Tax Sanctions on Individual Taxpayer Compliance at Pondok Aren Tax Service Office for the period 2019-2023. The increase in the number of registered taxpayers not accompanied by improved compliance quality, demonstrated by the surge in Tax Collection Letter issuance from 605 (2019) to 2,807 (2022) and persistent tax arrears exceeding 400 million rupiah, serves as the background for the urgency of this research. The research method employed is quantitative with a causal associative approach using multiple linear regression analysis. The research population consists of all Individual Taxpayers registered at Pondok Aren Tax Service Office totaling 405,809 individuals, with a sample of 100 respondents determined using the Slovin formula and convenience sampling technique. Data were collected through Likert-scale questionnaires and analyzed using SPSS version 26. The research findings indicate that: (1) Tax Collection Letter and Tax Sanctions simultaneously have a positive and significant effect on Individual Taxpayer Compliance with an F value of 52.227 > F table 3.09 and a contribution of 50.9%; (2) Tax Collection Letter partially has a positive and significant effect with a t value of 9.056 > t table 1.987 and is the dominant variable; (3) Tax Sanctions partially have a positive and significant effect with a t value of 6.086 > t table 1.987. This research confirms Attribution Theory and Compliance Theory in the Indonesian taxation context, where the combination of collection mechanisms (Tax Collection Letter) and legal consequences (sanctions) creates an effective enforcement system in promoting taxpayer compliance.